Purification and characterization of a thermoalkaline, cellulase free thermostable xylanase from a newly isolated Anoxybacillus sp. Ip-C from hot spring of Ladakh - Hauli, Ipsit; Sarkar, Bidisha; Mukherjee, Trinetra; Mukhopadhyay, Subhra Kanti (Research in Biotechnology, 2013)
An alkaline, highly thermostable cellulase free xylanase was purified from a thermophilic Anoxybacillus sp. Ip-C, newly isolated from hot spring of Ladakh. The enzyme was purified using ammonia sulphate precipitation followed by Sephadex G-75. The molecular weight of the xylanase was about 45 kDa, as analyzed by SDS-PAGE. The enzyme had optimum activity at pH 9.0 and 70ºC temperature; the enzyme retained 90% of its original activity for 96 hrs at 70 ºC. Vmax and Km of the enzyme were found to be 13.5 µmol min-1 mg-1 protein and 4.59 mg ml-1, respectively. Metal ions, Ca+2, Fe+2 and Mg+2 highly enhance the enzyme activity to 122.45, 119.06 and 118.98% respectively; whereas SDS and Hg+2 completely inhibit (0 U/ml) the enzyme activity. TLC analysis of enzymatic hydrolysis products showed that this xylanase is an endoxylanase, and generates xylooligosaccharides. Thus, it provides a potential thermostable alkaline xylanase for industrial applications.